The Effect of Audit Opinion, Reputation of Public Accounting Firm on Audit Delay with Audit Tenure as Moderation in Indonesian Manufacturing Companies - Teguh Widodo; Khanifah Khanifah; Wulan Budi Astuti; Salsa Hidayatusshiva (Universitas Wahid Hasyim Semarang, 2022)
This study aims to analyze audit opinion and KAP reputation that affect audit delay with audit tenure as a moderator in manufacturing companies listed on the Indonesia Stock Exchange in 2018 – 2020. In this study, audit opinion and KAP reputation are independent variables, and audit delay is a variable. dependent, tenure audit as a moderating variable. The population of this research is all manufacturing companies listed on the Indonesia Stock Exchange in 2018 – 2020. The total sample used is 135 companies which were determined through purposive sampling. The data analysis technique used is multiple linear analysis techniques with the help of the IBM SPSS 25 program. The results of this study indicate that audit opinion has no effect on audit delay. KAP reputation affects audit delay.